EDP‐297: A novel, farnesoid X receptor agonist—Results of a phase I study in healthy subjects. Issue 2 (21st November 2022) - Marotta, Christine; Ahmad, Alaa; Luo, Ed; Oosterhaven, Jart; van Marle, Sjoerd; Adda, Nathalie
Abstract: EDP‐297 is a farnesoid X receptor agonist under development for treating nonalcoholic steatohepatitis. The pharmacokinetic (PK), pharmacodynamic (PD), food effect, and safety were evaluated in a single ascending dose (SAD) and multiple ascending dose (MAD) phase I study. Healthy subjects received single EDP‐297 doses of 20–600 μg or once daily doses of 5–90 μg for 14 days. Safety, PKs, and PDs were assessed, including fibroblast growth factor 19 (FGF‐19) and 7‐α‐hydroxy‐4‐cholesten‐3‐one (C4). Among 82 subjects, EDP‐297 was generally well‐tolerated. Pruritus was observed in four subjects in the SAD phase and seven subjects in the MAD phase; four severe cases occurred at 90 μg in the MAD phase, including one that led to drug discontinuation. A grade 2 elevation in alanine aminotransferase occurred with 90 μg. Mean lipid values remained within normal range. Plasma exposures of EDP‐297 increased with SADs and MADs, with mean half‐life following multiple doses of 9–12.5 h. No food effect was observed. Mean FGF‐19 increased and C4 decreased up to 95% and 92%, respectively. EDP‐297 was generally well‐tolerated up to 60 μg MAD, with linear PKs suitable for once daily oral dosing, target engagement, and no food effect.